2021
DOI: 10.1515/nanoph-2021-0249
|View full text |Cite
|
Sign up to set email alerts
|

Few picosecond dynamics of intraband transitions in THz HgTe nanocrystals

Abstract: Optoelectronic devices based on intraband or intersublevel transitions in semiconductors are important building blocks of the current THz technology. Large nanocrystals (NCs) of Mercury telluride (HgTe) are promising semiconductor candidates owing to their intraband absorption peak tunable from 60 THz to 4 THz. However, the physical nature of this THz absorption remains elusive as, in this spectral range, quantum confinement and Coulomb repulsion effects can coexist. Further, the carrier dynamics at low energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…Then, the electron cools from 1P e to 1S e (end of regime I); this relaxation time τ P→S has been found to be 3.5 ps. This duration is in line with the intraband relaxation dynamics in CdSe or HgTe nanocrystals for which the relaxation decay is found to be in a 1–10 ps range . Note that in the case of pristine HgTe, only a negative signal is observed (middle panel of Figure a).…”
supporting
confidence: 83%
“…Then, the electron cools from 1P e to 1S e (end of regime I); this relaxation time τ P→S has been found to be 3.5 ps. This duration is in line with the intraband relaxation dynamics in CdSe or HgTe nanocrystals for which the relaxation decay is found to be in a 1–10 ps range . Note that in the case of pristine HgTe, only a negative signal is observed (middle panel of Figure a).…”
supporting
confidence: 83%
“…Later, Apretna et al investigated the carrier dynamics in such THz-absorbing HgTe NCs. 26 They found that intraband relaxation occurs within a few picoseconds and with a decay rate of 0.5 eV ps −1 , which is close to the values observed in more strongly confined HgTe NCs with sparser densities of states. 4,27 The THz HgTe NCs offer an interesting playground for probing an electronic state between the bulk and the strongly confined regimes.…”
supporting
confidence: 62%
“…Furthermore, negligible fluence dependence on the cooling rates suggests that multiparticle scattering processes play only a minor role in carrier cooling which is consistent with a very recent report of intraband dynamics in THz HgTe quantum dots. 39 This conclusion is further supported by the unaltered cooling rate found for excitations in the MEG regime.…”
Section: Discussionmentioning
confidence: 65%
“…Consequently, multiparticle scattering appears to play only a minor role in intraband relaxation in these quantum dots as also reported for much larger THz-gap HgTe crystallites. 39 In the following discussion, the mean value of the cooling times for each excitation wavelength in Fig. 3 is used as a more precise value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation